Diabetes mellitus: knowledge and perception on the role of community pharmacist among the general public - Anawi, Siti Nur Hafizah (2016)
Diabetes mellitus is one of the chronic diseases that are currently rising in its prevalence worldwide. An understanding of the level of knowledge in diabetes and perception towards community pharmacist in diabetes management among general public may thus be helpful in promoting a healthier lifestyle. The aims for this study are to evaluate the level of knowledge of diabetes among general public and to determine the public's perception on pharmacist's role in diabetes management. This study is a cross sectional study and was conducted in Ampang. Respondents were approached randomly at a train station, shopping mall, pharmacy and residential areas. There were 3 main sections in the questionnaire which were demographic, knowledge of diabetes in different aspects and perception of community pharmacist role in diabetes management. A total of 164 of general public residing in Ampang participated in this survey. Majority of them were female (57.3%) ranging from 18- 24 years old (52.4%), had a family history of diabetes (54.9%) and not a diabetic patient (87.8%). There were fair knowledge on diabetes with the "correct response" percentages for the each questions from every sections ranges from 43.9 to 87.2% (General knowledge), 40.2 to 90.9% (Risk factors), 36.6 to 79.9% (Symptoms), 30.5 to 72.0% (Complications), and 32.9 to 91.5% (Treatments and managements). Age, employment status, income level, family history on diabetes and diabetes status were found statistically significantly associated with the level of knowledge of diabetes. Community pharmacists were mainly perceived as a professional to clarify the information of diabetes medication (84.8%). The results of this study could contribute positively in future educational programs with more attention on areas of weaknesses thus increase the level of public awareness of diabetes as well as the role of community pharmacist in diabetes management.